The Teaching Factory-Based BMC Application Model for Improving Students’ Creativity of Central Java Public Vocational High Schools in Semarang - Lestari, Emi; Rusdarti, Rusdarti; Widiyanto, Widiyanto (Journal of Economic Education, 2021)
This study aims to analyze the BMC application model, as well as the validity, practicality, and effectiveness of the Teaching Factory-based BMC Application Model for Improving Student Creativity at Central Java Public Vocational Schools in Semarang. The research was conducted using the Research and development (R&D) method with the 4D development model (define, design, develop, disseminate). The preliminary study stage in this study used open interview observations from the teacher’s statements. The development stage of the BMC application model includes product design validated by experts, then implemented into learning tools that would be validated by practitioners as model users before being applied in the classroom to improve student creativity. The results of this study indicate that the Teaching Factory-Based BMC Application Model is valid according to the triangulation of sources through credibility, transferability, and dependability, conformability. Based on the practicality questionnaire and interview guidelines given by 105 students and 5 teachers, the results are "very practical". Based on the assessment of the effectiveness using the t-test with a significance level of 95%, the probability value/ P value of the paired t-test is 0.000 <0.05. Gain test with the average gain of 0.490 is in the medium category, meaning that students experience increased creativity after implementing the Teaching Factory-based BMC application model and is effectively used to improve student creativity.